Investigating ladybird alkaloids as potential leads for novel insecticides - Richards, David Philip (2016)
Ladybird beetles produce a range of alkaloid compounds which are found a high concentration in the haemolymph and released in response to perceived threat. These alkaloids are thought to function as agents of chemical defence and a small number have been shown to antagonise the nicotinic acetylcholine receptor. As intraguild predators, the chemical defence may be under selective pressure from other predatory insects, the alkaloids may therefore have evolved to target insects predominantly. To discover if other ladybird alkaloids show activity at nAChRs and investigate mode of action, alkaloids were extracted from 7-spot, 10-spot, 14-spot, cream spot, pine, orange and harlequin ladybird beetles and purified with acid-base separation. These species are each known to produce a different subset of alkaloids. Their action on nicotinic acetylcholine receptors was investigated by constructing concentration-inhibition plots by co-applying alkaloid extracts with acetylcholine to human embryonic muscle-type of TE671 cells and locust neuronal nAChRs. Peak current, net-charge and late (1 s) current were measured with whole-cell patch-clamp at VH = -75 mV. All alkaloid extracts antagonised the ACh responses of both cell types but potency and selectivity varied. The late current was the most strongly affected current parameter and the most potent antagonists of locust 1 s currents were alkaloids produced by 10-spot, 7-spot, pine and harlequin ladybird with IC50s ranging from 0.29–0.76 μg/mL. The 14-spot, cream spot and orange ladybird alkaloids had higher IC50s, ranging from 1.6-4.9 μg/mL. The IC50 values calculated for all species with, the exception of harlequin and orange ladybirds were significantly lower for locust than human nAChRs and these ranged from 1.3–47.8 μg/mL. The alkaloid extract that showed the highest selectivity for locust nAChRs was that of the 7-spot ladybird, with an IC50 value 58.4 fold lower. The alkaloids of the 10-spot, 14-spot, cream spot and pine ladybird also showed significantly higher potency for locust nAChRs over human nAChRs with IC50s 10.3–35 fold lower. Orange and harlequin ladybird alkaloids did not show higher potency for locust nAChRs. Harlequin ladybird alkaloids were highly potent to the nAChRs of both cell types whereas orange ladybird alkaloids showed low activity. The differences in potency correspond with differences in ecology, with the species that showed highest insect potency often found in close association with other predatory ladybird species. Those that showed low insect potency are arboreal specialists that are less likely to encounter insect predators. To investigate mode of action, ACh concentration-response curves in the presence and absence of harlequin ladybird alkaloid extract were constructed using TE671 cells. Increasing ACh concentrations were unable to overcome the inhibition caused by this alkaloid extract, indicating non-competitive action. Fitting the Woodhull equation to IC50 values calculated at holding potentials of 50, -50, -75, -100 and -120 mV revealed that the antagonism caused by this alkaloid extract was voltagedependent (P = 0.012), with late current IC50s of 23.1, 15.5 and 6 μg/mL at holding potentials of +50, -50 and -120 mV respectively. These data indicate that the active alkaloid(s) within this extract bind at an allosteric site and the strong voltagedependence of inhibition suggests mode of action is open-channel block rather than enhancement of desensitisation. The alkaloid harmonine was separated from other components of the alkaloid extract by thin-layer chromatography and the inhibitory activity tested against both human and locust nAChRs at VH = -75 mV. Both fractions were found to be active and displayed similar inhibitory activity towards human nAChRs with IC50s of 1.68 μg/mL for harmonine and 4.77 μg/mL for other alkaloid compounds. Harmonine was found to be significantly more potent towards locust nAChRs with an IC50 of 0.072 μg/mL as opposed to 3.23 μg/mL. This could indicate that harlequin ladybirds produce several alkaloids with different functions; harmonine may act as a chemical defence compound targeted towards insect predators. The alkaloid extract of the 10-spot ladybird was found to show significantly higher potency towards locust nAChRs than human. One of two alkaloids produced by this species is (-)-adaline. Synthetic (-)-adaline displayed identical inhibitory activity towards both cell types as the alkaloid extract of the 10-spot ladybird. Potency was significantly higher towards locust nAChRs than human, with IC50s of 10.26–45.83 μM against human and 0.55–2.97 μM against locust nAChRs. ACh concentration-response curves showed that (-)-adaline acts non-competitively and IC50 values at different holding potentials reveal that it is strongly voltage-dependent (P = 0.003 in human and P = 0.007 in locust nAChRs) and inactive at positive holding potentials. As with the alkaloid extract of the harlequin ladybird, this alkaloid acts as a non-competitive negative allosteric modulator which shows higher potency for locust over human nAChRs and strong voltage-dependence of inhibition, consistent with open-channel block. A structurally diverse range of ladybird alkaloids displayed inhibitory activity towards both human and insect nAChRs. This inhibition was non-competitive and voltage-dependent for both harlequin ladybird alkaloid extract and adaline, indicating that these alkaloids act as negative allosteric modulators, possibly open-channel blockers. The majority of ladybird alkaloid extracts tested were significantly more potent towards insect than human nAChRs. It remains to be seen whether the activity of these compounds is restricted to the nAChRs, or whether they act as non-selective pore blockers. Ladybird alkaloids appear to represent a library of novel nAChR antagonists, some of which could be further investigated as potential insecticide leads.